Essentials and guidelines for clinical medical physics residency training programs: executive summary of AAPM Report Number 249. (8th May 2014) - Prisciandaro, Joann I.; Willis, Charles E.; Burmeister, Jay W.; Clarke, Geoffrey D.; Das, Rupak K.; Esthappan, Jacqueline; Gerbi, Bruce J.; Harkness, Beth A.; Patton, James A.; Peck, Donald J.; Pizzutiello Jr, Robert J.; Sandison, George A.; et al.
Abstract : There is a clear need for established standards for medical physics residency training. The complexity of techniques in imaging, nuclear medicine, and radiation oncology continues to increase with each passing year. It is therefore imperative that training requirements and competencies are routinely reviewed and updated to reflect the changing environment in hospitals and clinics across the country. In 2010, the AAPM Work Group on Periodic Review of Medical Physics Residency Training was formed and charged with updating AAPM Report Number 90 . This work group includes AAPM members with extensive experience in clinical, professional, and educational aspects of medical physics. The resulting report, AAPM Report Number 249, concentrates on the clinical and professional knowledge needed to function independently as a practicing medical physicist in the areas of radiation oncology, imaging, and nuclear medicine, and constitutes a revision to AAPM Report Number 90 . This manuscript presents an executive summary of AAPM Report Number 249 . PACS number: 87.10.‐e